AGRI ROBOT FOR MULTIPURPOSE APPLICATIONS (International Journal of Food and Nutritional Sciences, 2022)
The project presents about the multiple agricultural tasks done by the single robot. To develop the efficiency of the agricultural tasks we have to find the new ways. This project deals with a novel approach for cultivating lands in very efficient way. The distinctiveness of this agriculture robot system is it is multitasking abilities which can drill, pick and place, seeding, pumping water & fertilizers, weather monitoring to work in both agriculture, forestation and gardening platform. The project aim is design, development and the fabrication of the robot which can dig soil, put seeds, roller to close the mud and sprayer to spray water, this whole system of robot works with the help of battery and solar power. More than 40% of the population in the world chooses agriculture as the primary occupation, in recent years the development of the autonomous vehicles in the agriculture has experienced increased interest.